A virilized patient with congenital hemihypertrophy. Issue 828 (October 1994) - Mark, S.; Clark, O. H.; Kaplan, R. A.
Abstract : An 18 year old woman with congenital hemihypertrophy of her left side, presented with the rapid onset of virilism, hypertension and a cushingoid appearance. A computed tomographic examination revealed adrenal and hepatic masses. Adrenocortical carcinoma was confirmed by surgical pathology. Hemihypertrophy is linked to a variety of benign and malignant disorders that usually appear during childhood. These disorders include adrenocortical carcinoma and hepatoblastoma. We bring this case to clinical attention to increase awareness that adult patients with congenital hemihypertrophy are still at a significant risk of developing neoplasms.